On transport of reactive solute in a pulsatile Casson fluid flow through an annulus. Issue 11 (1st November 2020) - Debnath, S.; Saha, A. K.; Mazumder, B. S.; Roy, A. K.
Abstract : This paper examines the effect of heterogeneous chemical reaction on the transport of a solute in a Casson fluid flow through an annular pipe under a periodic pressure gradient. Aris–Barton's method of moments is employed to understand the transport process. A finite difference implicit scheme is utilized to solve the momentum equation as well as the integral moment equation arising from the unsteady convective diffusion equation. Using the Hermite polynomial representation, the mean concentration distribution in the axial direction is acquired from the first four central moments. The transport phenomenon is discussed by three transport coefficients, namely exchange, advection, and dispersion coefficients owing to wall reactions, yield stress, radius ratio, etc. The present study can, therefore, be helpful to understand the transport process in blood flow through arteries.